End‐stage renal disease as an independent risk factor for in‐hospital mortality after coronary drug‐eluting stenting: Understanding and modeling the risk. Issue 2 (19th May 2020) - Dunn, Aaron N.; Huded, Chetan; Simpfendorfer, Conrad; Raymond, Russell; Kapadia, Samir; Tuzcu, E. Murat; Ellis, Stephen G.
Abstract: Objectives: We sought to compare in‐hospital outcomes between patients with and without end‐stage renal disease (ESRD) undergoing coronary drug‐eluting stent (DES) placement and to model risk of in‐hospital adverse postpercutaneous coronary intervention (PCI) events in ESRD patients. Background: The effect of ESRD on the risk of in‐hospital complications after DES PCI is relatively unclear, as is the ability to prospectively stratify risk in this population. Methods: Consecutive patients undergoing first‐time DES between April 1, 2003 and June 30, 2018 at a single tertiary care hospital were included in a prospective registry. Outcomes in those with ESRD were compared to those without ESRD. The primary endpoint was in‐hospital all‐cause mortality; secondary endpoints included in‐hospital major adverse cardiac events (MACE)—defined as cardiac death, myocardial infarction, or unplanned revascularization—and major bleeding. Multivariate logistic regression modeling was used to identify factors associated with each outcome and to generate risk scores. Results: Among 18, 134 patients in the study population, 382 (2.1%) had ESRD. ESRD was associated with increased risk of in‐hospital mortality (7.1 vs. 2.9%, p  < .001), in‐hospital MACE (6.3 vs. 2.1%, p  < .001), and major bleeding (12.0 vs. 2.6%, p  < .001). After multivariable risk adjustment, ESRD was independently associated with in‐hospital mortality (odds ratio: 1.83, 95% confidence interval: 1.04–3.23, p  = .04) but not MACE or major bleeding. Among patients with ESRD, risks of MACE and major bleeding were successfully modeled ( c ‐statistics = .72 and .85, respectively). Conclusions: ESRD is independently associated with increased risk of in‐hospital mortality after coronary DES. Future studies are necessary to validate risk models derived to identify high‐risk ESRD patients.